Potential Income of Palm Oil Farmers in Financing Higher Education at Jambi University - Tiara Sani, Ratna; Kuswanto, Kuswanto; Sahara, Sahara (International Journal of Education and Humanities, 2025)
This study aims to analyze the income potential of oil palm farmers in financing higher education at Jambi University, addressing the rising educational costs that burden farmer families. Using a descriptive quantitative method, data were collected through questionnaires from 30 oil palm farmers meeting specific criteria. The analysis employed descriptive statistics to examine income and expenditure patterns. Results showed that the average household income was IDR 6,838,083.33, with expenditures of IDR 2,695,366.63. The income generated from oil palm farming alone has the potential to exceed educational funding needs, with a potential income ratio (PP) of 1.09 for oil palm farming and 1.67 when combined with other sources. While most farmers demonstrate strong income potential, some with lower incomes require additional support. The combined income from oil palm and non-oil palm activities offers a better opportunity for financing education. Relying solely on oil palm income could limit financial stability. This research contributes insights into how farmers' income levels relate to their capacity to fund education and suggests policy recommendations to enhance access to higher education for farmers' children, fostering social and economic development in the area